Feminist disability studies vs discrimination of women with disabilities - KASPRZAK, TOMASZ (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Tomasz Kasprzak, Feminist disability studies vs discrimination of women with disabilities. Interdisciplinary Contexts of Special Pedagogy, no. 24, Poznań 2019. Pp. 127-138. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi. org/10.14746/ikps.2019.24.07 Disabled women are often treated as if they were deprived of feelings or desires.They are exposed to discrimination not only because of disability, but also because of gender (multiple discrimination). Feminist disability studies are an interdisciplinary field of research into the socio-political situation of women with disabilities.